Dispersion of carbon nanotubes in organic solvent by commercial polymers with ethylene chains: Experimental and theoretical studies. (10th February 2015) - Shigeta, Masahiro; Kamiya, Katsumasa; Uejima, Mitsugu; Okada, Susumu
Abstract: We demonstrate the possible candidate dispersion agents that can uniformly disperse carbon nanotubes (CNTs) into organic solvent, from among commercially available polymers. We find that CNTs were well dispersed into dimethylacetamide with the use of polystyrene, poly(vinyl chloride), and poly(vinyl pyrrolidone) as dispersion agents. Theoretical calculations revealed that the dispersibility of these polymers arises from the moderate strength and preferential directionality of the interactions between the CNTs and the polymers.